Genomic characterization of the dominating Beta, V2 variant carrying vaccinated (Oxford−AstraZeneca) and nonvaccinated COVID‐19 patient samples in Bangladesh: A metagenomics and whole‐genome approach. Issue 4 (7th January 2022) - Rahaman, Md. Mizanur; Sarkar, Md. Murshed Hasan; Rahman, M. Shaminur; Islam, M. Rafiul; Islam, Israt; Saha, Otun; Akter, Shahina; Banu, Tanjian Akhtar; Jahan, Iffat; Habib, Md. Ahasan; Goswami, Barna; Bari, Latiful; et al.
Abstract: Bangladesh is experiencing a second wave of COVID‐19 since March 2021, despite the nationwide vaccination drive with ChAdOx1 (Oxford−AstraZeneca) vaccine from early February 2021. Here, we characterized 19 nasopharyngeal swab (NPS) samples from COVID‐19 suspect patients using genomic and metagenomic approaches. Screening for SARS‐CoV‐2 by reverse transcriptase polymerase chain reaction and metagenomic sequencing revealed 17 samples of COVID‐19 positive (vaccinated = 10, nonvaccinated = 7) and 2 samples of COVID‐19 negative. We did not find any significant correlation between associated factors including vaccination status, age or sex of the patients, diversity or abundance of the coinfected organisms/pathogens, and the abundance of SARS‐CoV‐2. Though the first wave of the pandemic was dominated by clade 20B, Beta,  V2 (South African variant) dominated the second wave (January 2021 to May 2021), while the third wave (May 2021 to September 2021) was responsible for Delta variants of the epidemic in Bangladesh including both vaccinated and unvaccinated infections. Noteworthily, the receptor binding domain (RBD) region of S protein of all the isolates harbored similar substitutions including K417N, E484K, and N501Y that signify the Beta, while D614G, D215G, D80A, A67V, L18F, and A701V substitutions were commonly found in the non‐RBD region of Spike proteins. ORF7b and ORF3a genes underwent a positive selection (d N /d S ratio 1.77 and 1.24, respectively), while the overall S protein of the Bangladeshi SARS‐CoV‐2 isolates underwent negative selection pressure (d N /d S  = 0.621). Furthermore, we found different bacterial coinfections like Streptococcus agalactiae, Neisseria meningitidis, Elizabethkingia anophelis, Stenotrophomonas maltophilia, Klebsiella pneumoniae, and Pseudomonas plecoglossicida, expressing a number of antibiotic resistance genes such as tet A and tet M. Overall, this approach provides valuable insights on the SARS‐CoV‐2 genomes and microbiome composition from both vaccinated and nonvaccinated patients in Bangladesh. Highlights: The first wave was dominated by clade 20B, the second wave was dominated by Beta, V2 variant, and the third wave was responsible for Delta variants in Bangladesh. The first dose of the Oxford−AstraZeneca vaccine could not protect from the Beta, V2 variant in Bangladesh. Different bacterial coinfections like Streptococcus agalactiae, Neisseria meningitidis, Elizabethkingia anophelis, Stenotrophomonas maltophilia, Klebsiella pneumoniae, and Pseudomonas plecoglossicida, expressing a number of antibiotic resistance genes such as tet A and tet M.